1982
DOI: 10.1128/aac.21.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of the copper(I) complex of 2,9-dimethyl-1,10-phenanthroline on Mycoplasma gallisepticum

Abstract: Evidence was found that the inhibitory action of Cu(DMP)2NO3, the copper(I) complex of 2,9-dimethyl-1,10-phenanthroline (DMP), on Mycoplasma gallisepticum is a consequence of the ultimate toxicity of copper, and not that of the ligand, DMP. From uptake studies with radiolabeled 67Cu and [14C]DMP, we concluded that significantly more copper than DMP is bound to the mycoplasmal cell. It appeared that dissociation of Cu(DMP)2+ occurred shortly after interaction with the cell membrane. Copper was transported acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…First, we examined the antimicrobial activity of Neo against human mollicutes. Neo activity has previously been examined on a closely related avian mycoplasma, M. gallisepticum , and its antimicrobial activity was shown to be Cu-dependent (Smit et al, 1982; Gaisser et al, 1987a,b; de Zwart et al, 1991). The ureaplasma strains showed differential susceptibility to Neo in vitro (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we examined the antimicrobial activity of Neo against human mollicutes. Neo activity has previously been examined on a closely related avian mycoplasma, M. gallisepticum , and its antimicrobial activity was shown to be Cu-dependent (Smit et al, 1982; Gaisser et al, 1987a,b; de Zwart et al, 1991). The ureaplasma strains showed differential susceptibility to Neo in vitro (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previously published work with S. aureus and M. tuberculosis has demonstrated that compounds that chelate copper can exhibit antibacterial effects (Dalecki et al, 2016; Shah et al, 2016). Previous work in another laboratory during the 1980s examined the effect of Neo on Cu stress with M. gallisepticum (Smit et al, 1982; Gaisser et al, 1987b). The mechanism of action for Neo was determined to be the result of copper toxicity, and not that of the ligand itself (Smit et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antimycoplasmal activity of a series of bipyridyl analogues has been found to be de pendent on the transport of Cu+ ions across the mycoplasmal membrane by these com pounds [1][2][3]. The purpose of the present study was to investigate whether the composi tion of the membrane of different types of or ganisms would influence the inhibitory activ-…”
Section: Introductionmentioning
confidence: 99%